Peran Orangtua dalam Krisis Remaja - Peter, Ramot (Humaniora, 2015)
Crisis in youth will impact his/her personal growth, attitude, and negative sense in emotional response. The negative sense in emotional response will drive his/her action to do bad things and will disturb his/her life. To understand the negative emotional attitude when youth facing crisis, parents need to understand the crisis period, the roles, and the responsibilities of parents to help the youth overcome the crisis. The explanation is given by using qualitative data analysis and conducted concurrently with gathering data, making interpretations, and writing report. The study shows the negative emotional response of youth will impact the negative attitudes and actions. In this case, parents must guide the youth for spiritual mindsets in order to affect positive emotional attitudes and actions. The positive spiritual action will be reflected by understanding the God’s Words in solving the problem, finding the way out, and overcoming the crisis. Hence, the youth crisis is not a disaster, but the reflection to reach the positive improvement.